Information technology law - Rowland, Diane; Kohl, Uta.; Charlesworth, Andrew, 1966- (Abingdon, Oxon ; New York : Routledge, 2012)
"This fourth edition of Information Technology Law has been completely revised in the light of developments within the field since publication of the first edition in 1997. Now dedicated to a more detailed analysis of and commentary on the latest developments within this burgeoning field of law, this new edition is an essential read for all those interested in the interface between law and technology and the effect of new technological developments on the law. New additions to the fourth edition include: - analysis of regulatory issues and jurisdictional questions - specific consideration of intermediary liability - developments in privacy and data protection - extension of computer crime laws - developments in software patents - open source software and the legal implications"--
Regulating information technologies -- Regulatory competence over the Internet -- Content regulation : liability of intermediaries -- Cyber crime -- Privacy and data protection -- Surveillance, data retention and encryption -- Electronic commerce -- Domain names -- Copyright and the Internet -- Intellectual property rights in software -- Software licences and open-source software licensing (IF/OSSI), and "software as a service" (SaaS) -- Defective software.
Includes bibliographical references (p. [489]-521) and index.
Keywords: Computers -- Law and legislation -- Great Britain; Internet -- Law and legislation -- Great Britain; Data protection -- Law and legislation -- Great Britain; Electronic commerce -- Law and legislation -- Great Britain; Copyright -- Computer programs -- Great Britain; Computer software -- Law and legislation -- Great Britain; Information technology -- Great Britain; LAW / General; LAW / Science & Technology